2021
DOI: 10.31235/osf.io/q87fu
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Equity in new active travel infrastructure: a spatial analysis of London’s new Low Traffic Neighbourhoods

Abstract: In this article we examine equity in new active travel infrastructure in London, UK. We focus on Low Traffic Neighbourhood schemes (LTNs) introduced during Covid-19. These mainly involve ‘modal filters’ that restrict through motor traffic from residential streets. Such approaches to traffic management are traditional in the Netherlands, but relatively new in London and other global cities such as Barcelona. LTNs are often controversial, with one criticism being that they are implemented in affluent areas and h… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 33 publications
0
1
0
Order By: Relevance
“…Similar measures have been placed on buses, with the city committed to phasing out diesel buses by 2037 in order to bring the city's air pollution concentrations within acceptable limits. Low-traffic neighbourhoods may help to reduce exposure inequities, as low-income households are more likely to live within them in London (Aldred et al 2021).…”
Section: Improving Outdoor Environmentsmentioning
confidence: 99%
“…Similar measures have been placed on buses, with the city committed to phasing out diesel buses by 2037 in order to bring the city's air pollution concentrations within acceptable limits. Low-traffic neighbourhoods may help to reduce exposure inequities, as low-income households are more likely to live within them in London (Aldred et al 2021).…”
Section: Improving Outdoor Environmentsmentioning
confidence: 99%
“…Steinbach, Grundy, et al (2011) found that the implementation of 20 mph zones in London targeted mostly deprived areas and that this helped to mitigate socioeconomic inequalities in road injury. Most recently, Aldred et al (2021) found that the Low traffic neighbourhood (LTN) schemes, set up in London during Covid-19, were overall equitably distributed.…”
Section: Access To Cycling Networkmentioning
confidence: 99%